(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The most important task of primary education is teaching children to read. At this stage, elementary school students should not only learn to read aloud and silently, but also use reading skills to find the necessary information from the text. Necessary knowledge, mastery of other subjects, enriches their learning experience and intelligence, because one of the characteristics of the new generation standard is personal skills such as self-esteem, self-development and self-awareness. is to develop qualities.